Serum cardiac Troponin T in adolescent runners: Effects of exercise intensity and duration - Fu, F.; Nie, J.; Tong, T. K. (International Journal of Sports Medicine, 2009)
The purpose of this study was to evaluate the interactive effects of exercise duration and intensity on the elevation of serum cardiac troponin T (cTnT) in trained adolescent athletes following prolonged exercise in a laboratory-based setting. Thirteen male adolescent runners (mean age 14.8±1.6 year) performed two 45-min and two 90-min constant-load treadmill runs with intensities set at the running speeds that corresponded to either 80% or 100% ventilatory threshold (Thvent): 80%Thvent45 min, 80%Thvent90 min, 100%Thvent45 min and 100%Thvent90 min. Serum cTnT was assessed pre and post exercise. In the 100%Thvent45 min trial, the post-exercise serum cTnT level [(Median) 0.015 ng.ml-1; (Range)<0.01-0.375 ng.ml-1] was greater than that of the 80%Thvent45 min (undetectable cTnT) and 80%Thvent90 min (detectable cTnT in two subjects, 0.021 and 0.133 ng.ml-1) trials (P<0.01). The serum cTnT level was further increased in the 100%Thvent90 min trial [(Median) 0.063 ng.ml-1; (Range)<0.01-0.417 ng.ml-1] when the treadmill run was sustained for an additional 45 min (P<0.05). Similar changes were observed in the cTnT positive rate in subjects. These findings suggest that exercise duration and intensity are essential factors in eliciting cTnT release interactively following an endurance exercise. Nevertheless, exercise intensity compared to duration appears to cause a more pronounced increase in cTnT levels.